Post-abortion contraceptive uptake, choices, and factors associated with it among women seeking abortion services in Africa: a systematic review and meta-analysis - Dagnew, Gizachew Worku; Asresie, Melash Belachew (Frontiers in Global Women's Health, 2025)
BackgroundIn Africa, over one-third of women experience multiple abortions, often due to inadequate access to effective modern contraceptives. This highlights a critical gap in understanding the patterns and predictors of post-abortion contraceptive (PAC) use. To address this issue, a systematic review and meta-analysis were conducted to assess the uptake of PAC and associated factors among African women who received abortion services.MethodsFollowing the PRISMA guideline, all articles published between January 1, 2015, and December 30, 2023, were systematically retrieved from multiple databases. Articles reporting PAC uptake among African women were included. The pooled prevalence of Post-abortion contraceptive uptake was determined using a random effects model. The variation between the included studies was assessed using a funnel plot and I2 heterogeneity statistics. Sources of heterogeneity: Subgroup analysis was performed by country, publication period, study design, and sub-African region.ResultsFrom 48 articles, a total of 84,205 women who underwent abortion services were included in the analysis. The pooled prevalence of PAC uptake in Africa was 58.78% (95% CI: 52.36–65.21), with high heterogeneity (I2 = 99.8%, 95% CI: 99.2%-99.9%; P < 0.001). The subgroup analysis revealed variation by country, publication period, and sub-African region. The most widely used contraceptive methods were injectables (30.27%), followed by implants (25.13%), oral contraceptive pills (22.34%), and IUDs (10.47%). Attending formal education (OR = 1.46, 95% CI = 1.03, 2.07), knowing the period of fertility (OR = 1.72, 95% CI = 1.14, 2.59), counseling about contraceptives (OR = 3.40, 95% CI = 1.82, 6.35), not having a desire for pregnancy (OR = 3.08, 95% CI = 1.74, 5.35, 95% CI = 2.55, 7.42), and possessing contraceptive knowledge (OR = 2.30, 95% CI = 1.41, 3.76) had a statistically significant combined effect on PAC uptake in Africa.ConclusionThe uptake of PAC in Africa stands at 58.78%, which is considered low according to the World Health Organization's recommendation that all women should postpone conception for six months following an abortion. There was also a decline of 20.22% between 2020 and 2023 compared to the pooled uptake between 2015 and 2019. To address this, it is crucial to enhance women's awareness of post-abortion contraception, the conception risks after abortion, and to strengthen client-centered counseling alongside women's education.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024505129, PROSPERO CRD42024505129.